Environmental Humanities Character of Gulliver in Swift’s Gulliver’s Travel - Arin Mantara Anggawirya; Rosalia Floriani; Marnina Marnina; Yuni Ratna Purwaningsih (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2022)
Abstract. This paper provides the environment ecosystem reflected in the Gulliver’s Travel: A Voyage to Lilliput. The theory used in this paper was the Ecocriticism approach to literature. This approach focuses on the literature that reflects the ecological system. The method used in collecting the data was close reading and note-taking. Then the researchers analyze the data by using genetic structuralism. Genetic structuralism mainly concerns the context of the text relates to the existence of reality. The environment in Gulliver’s Travel shows conditions from a Utopia perspective. Indication found in the form of Gulliver is a figure who acts as a war protector and abundant resources for Lilliput.           Keywords: ecocriticism; environmental humanities; Gulliver’s TravelAbstrak. Makalah ini menyajikan ekosistem lingkungan yang tercermin dalam Gulliver’s Travel: A Voyage to Lilliput. Teori yang digunakan dalam tulisan ini adalah pendekatan Ecocriticism pada sastra. Pendekatan ini berfokus pada literatur yang mencerminkan sistem ekologi. Metode yang digunakan dalam pengumpulan data adalah membaca saksama dan mencatat. Kemudian peneliti menganalisis data dengan menggunakan strukturalisme genetik. Strukturalisme genetik berfokus pada memperhatikan gagasan tentang konteks teks dan apa yang mungkin berhubungan dengan realita. Lingkungan pada Gulliver’s Travel menunjukan kondisi pada perspektif Utopia. Indikasi yang ditemukan berupa Gulliver merupakan Tokoh yang berperan sebagagi War Protector dan Sumberdaya yang melimpah bagi LilliputKata kunci: ekokritik; humanitas lingkungan; Gulliver’s Travel